Marr Mooditj Foundation: Three decades of Aboriginal health education - Winch, Marie Joan (Curtin University, 2010)
This thesis presents a history of Marr Mooditj Foundation, the Aboriginal health worker training college that has for the past thirty years provided culturally appropriate education in primary health care and training for Indigenous staff involved in delivering and managing health care and community service programs. It traces the development of Marr Mooditj from its origins in the context of Indigenous health in the 1970s through to its current achievements and challenges.This auto-ethnographic study, which focuses on my central positioning as an advocate and leader of Marr Mooditj, documents the history of how Marr Mooditj emerged from a context of ‘dis-ease’, where government legislation and the introduction of strict and repressive policies and practices regarding Indigenous people determined an outcome that resulted in a disruption of lifestyle, separation of children from families, serious illness, and an on-going, poverty-stricken separation from the rest of the population. It explores the wide-ranging ramifications of the appalling state of Indigenous health in Western Australia, and the part played by all those involved in establishing and running Marr Mooditj and the Perth Aboriginal Medical Service in working at changing this for the better. The thesis argues that Marr Mooditj Foundation is now deeply embedded within Aboriginal culture, is responsible for delivering culturally safe programs, and can be proud of its contribution to closing the gap between Aboriginal and mainstream health care in Australia.